2014
DOI: 10.1186/1556-276x-9-562
|View full text |Cite
|
Sign up to set email alerts
|

Post-annealed gallium and aluminum co-doped zinc oxide films applied in organic photovoltaic devices

Abstract: Gallium and aluminum co-doped zinc oxide (GAZO) films were produced by magnetron sputtering. The GAZO films were post-annealed in either vacuum or hydrogen microwave plasma. Vacuum- and hydrogen microwave plasma-annealed GAZO films show different surface morphologies and lattice structures. The surface roughness and the spacing between adjacent (002) planes decrease; grain growth occurs for the GAZO films after vacuum annealing. The surface roughness increases and nanocrystals are grown for the GAZO films afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Thus, the composition of A3.0G1.0ZO was found to be optimal with respect to electrical properties, showing both the highest measured mobility and charge carrier density. Whilst the charge carrier density was lower than that reported elsewhere by up to four times, 38,39,43,44 this can in turn rationalize the exceptionally high carrier mobility (10 times higher than that reported by the best performing AGZO materials) [38][39][40][41][42][43][44] in part due to reduced scattering effects from other charge carriers.…”
Section: Electrical Characterizationmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, the composition of A3.0G1.0ZO was found to be optimal with respect to electrical properties, showing both the highest measured mobility and charge carrier density. Whilst the charge carrier density was lower than that reported elsewhere by up to four times, 38,39,43,44 this can in turn rationalize the exceptionally high carrier mobility (10 times higher than that reported by the best performing AGZO materials) [38][39][40][41][42][43][44] in part due to reduced scattering effects from other charge carriers.…”
Section: Electrical Characterizationmentioning
confidence: 90%
“…The co-doping approach has yielded films with resistivities in the literature of ca. 10 -4 Ω cm [38][39][40][41][42][43] and optical transparencies above 80 % [42][43][44] for thin films (deposited by magnetron sputtering). Whilst showing promise for TCO applications, AGZO has received relatively little attention in the literature compared to singularly doped AZO and GZO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-annealing has been shown to improve the electrical and optical properties of as-deposited AZO/ITO films and reduce emissivity. In addition, our research team reported the effects of substrate temperature, vacuum annealing and hydrogen plasma annealing, respectively, on the structure and electrical and optical properties of GAZO films [28,30,31]. According to previous reports, the processing time of hydrogen plasma treatment can affect the structure of GAZO films and thus their physical properties [30,31].…”
Section: Introductionmentioning
confidence: 98%
“…Aluminum (Al) and gallium (Ga) are n-type dopants that increase the concentration of free electrons, thereby improving the conductivity of ZnO films [7,8]. Al-doping of ZnO (AZO) had shown higher reactivity and optical transmittance than ZnO and is preferred dopant for the fabrication of transducer devices [8,9].…”
Section: Introductionmentioning
confidence: 99%